An analysis of Islamic holy scriptures in terms of patriarchy - Erkan, Mustafa Serdar (İstanbul Bilgi Üniversitesi, 2020)
ABSTRACT: In this thesis, after the definition, structure and foundations of patriarchy were explained according to various sources, the patriarchal nature of the Qur’an was investigated with the help of a content analyses by reading the Qur’anic verses revealed in Mecca and Medina, and whether this patriarchy gradually and systematically changes according to the chronological revelation order of the verses was examined. Whether Islam at its core is a masculine religion is a controversial subject with differing views. As there are those who argue that Islam is an egalitarian religion that liberates women, there are also those who claim it to be a patriarchal religion which considers women to be second-class compared to men. According to the latter view, men are deemed superior to women in Islam and are given the right to rule over them, leaving women with the duties of giving birth and obeying men. Proponents of both views base their claims on the Qur'an itself. By examining these different views, I tried to reach a conclusion in the second part of thesis about the structure of patriarchy in the Qur'an by analyzing the Qur’anic verses qualitatively on certain issues such as creation, male and female behavioral patterns, marriage, divorce, concubinage, polygamy, veiling of women, testimony, and inheritance by tracing the social events that might affect the formation of patriarchy.

ÖZET: Bu tezde, ilk bölümde ataerkilliğin tanımı, yapısı ve oturduğu temeller çeşitli kaynaklar eşliğinde açıklandıktan sonra, Mekke ve Medine’de inen ayet okumaları ve analizleri üzerinden Kuran'ın ataerkil niteliği kantitatif yönden araştırılmış ve bu ataerkilliğin ayetlerin kronolojik iniş sırasına göre sistematik olarak değişip değişmediği incelenmiştir. İslam’ın özünde ataerkil bir din olup olmadığı tartışmalıdır. İslam'ın kadınları özgürleştiren, eşitlikçi bir din olduğunu iddia edenler olduğu gibi, kadınları erkeklere göre ikinci sınıf olarak gören ataerkil bir din olduğunu savunanlar da vardır. Bu ikinci görüştekilere göre erkekler İslam'da kadınlardan üstün kabul edilir ve kadınların sadece çocuk doğurma ve erkeklere itaat etme görevleri vardır. Erkeklere ise kadınları yönetme hakkı verilmiştir. Her iki görüşü savunanlar da iddialarını Kuran’a dayandırmaktadır. İkinci bölümde ise bu farklı görüşler incelenerek Kuran ayetleri ataerkillik yönünden, yaratılış, erkek ve kadın davranış kalıpları, evlilik, boşanma, cariyelik, çok eşlilik, kadınların örtünme zorunluluğu, tanıklık ve miras gibi konularda kalitatif yönden analiz edilmiş ve bu ataerkilliğin oluşumunu etkileyen sosyal olayların izi sürülerek Kuran'daki ataerkil yapı hakkında bir sonuca ulaşılmaya çalışılmıştır
İslamın kutsal metinlerinin ataerkillik yönünden analizi
Keywords: Ataerkillik; Analiz; Kuran; Kronoloji; Ayet; Patriarchy; Analysis; Qur'an; Chronology; Verse